Metabolic Disorders and Male Hypogonadotropic Hypogonadism - Pivonello, Rosario; Menafra, Davide; Riccio, Enrico; Garifalos, Francesco; Mazzella, Marco; de Angelis, Cristina; Colao, Annamaria (Frontiers in Endocrinology, 2019)
Several studies highlight that testosterone deficiency is associated with, and predicts, an increased risk of developing metabolic disorders, and, on the other hand, is highly prevalent in obesity, metabolic syndrome and type-2 diabetes mellitus. Models of gonadotropin releasing hormone deficiency, and androgen deprivation therapy in patients with prostate cancer, suggest that hypogonadotropic hypogonadism might contribute to the onset or worsening of metabolic conditions, by increasing visceral adiposity and insulin resistance. Nevertheless, in functional hypogonadism, as well as in late onset hypogonadism, the relationship between hypogonadotropic hypogonadism and metabolic disorders is bidirectional, and a vicious circle between the two components has been documented. The mechanisms underlying the crosstalk between testosterone deficiency and metabolic disorders include increased visceral adipose tissue and insulin resistance, leading to development of metabolic disorders, which in turn contribute to a further reduction of testosterone levels. The decrease in testosterone levels might be determined by insulin resistance-mediated and, possibly, pro-inflammatory cytokine-mediated decrease of sex hormone binding globulin, resulting in a temporary increased free testosterone available for aromatization to estradiol in visceral adipose tissue, followed by a subsequent decrease in free testosterone levels, due to the excess of visceral adipose tissue and aromatization; by a direct inhibitory effect of increased leptin levels on Leydig cells; and by a reduced gonadotropin secretion induced by estradiol, inflammatory mediators, leptin resistance, and insulin resistance, with the ultimate determination of a substantial hypogonadotropic hypogonadism. The majority of studies focusing on the effects of testosterone replacement therapy on metabolic profile reported a beneficial effect of testosterone on body weight, waist circumference, body mass index, body composition, cholesterol levels, and glycemic control. Consistently, several interventional studies demonstrated that correction of metabolic disorders, in particular with compounds displaying a greater impact on body weight and insulin resistance, improved testosterone levels. The aim of the current review is to provide a comprehensive overview on the relationship between hypogonadotropic hypogonadism and metabolism, by clarifying the independent role of testosterone deficiency in the pathogenesis of metabolic disorders, and by describing the relative role of testosterone deficiency and metabolic impairment, in the context of the bidirectional relationship between hypogonadism and metabolic diseases documented in functional hypogonadotropic hypogonadism. These aspects will be assessed by describing metabolic profile in men with hypogonadotropic hypogonadism, and androgenic status in men with metabolic disorders; afterwards, the reciprocal effects of testosterone replacement therapy and corrective interventions on metabolic derangements will be reported.